Successful Cardiopulmonary Resuscitation Rate and Related Factors in Emergency Departments - Touraj Assadi; Ali Asghar Manouchehri; Farzad Bozorgi; Iraj Goli Khatir; Solmaz Askari (Indian Journal of Forensic Medicine & Toxicology, 2021)
Cardiopulmonary Resuscitation, also called CPR, is a set of actions taken by conscious and willingindividuals to restore the functions of two vital heart and lung organs and deliver blood and oxygen to thebrain to prevent brain damage. This is an immediate intervention to prevent or delay death in a person whohas suddenly had a cardiopulmonary arrest. About 40 years have passed since the start of cardiopulmonaryresuscitation, so the survival rate is low. Research has shown that about 10 to 15 percent of people surviveafter resuscitation. Cardiac resuscitation is on the rise among hospitalized patients, so these measures andthe factors that contribute to its success are crucial.Our aim is to review the success rate of cardiopulmonaryresuscitation and its associated factors in emergency departments and hospitals. In this review study,keywords such as cardiopulmonary resuscitation, cardiopulmonary arrest, emergency, underlying cause,success rate, resuscitation outcome and related factors and search on reputable Google scientific databasesScholar, Pubmed, Web of Science, WHO Web site, Articles and theses published between 1989 and 2019,and finally a number of sources were selected and critiqued, interpreted, and analyzed. We concluded at thetime of cardiopulmonary arrest, the speed of technicians, equipment, and devices and medicines used willincrease the chances of successful cardiopulmonary resuscitation.